Sustainability Assessment of Fruit and Nut Crops in North Florida and North Central Florida - Peter Andersen; Kevin R. Athearn; Ali Sarkhosh; Jeffrey G. Williamson; Mercy Olmstead (EDIS)
Revised! HS765, a 16-page illustrated article by Peter C. Andersen, Kevin R. Athearn, Ali Sarkhosh, Mercy A. Olmstead, and Jeffrey G. Williamson, summarizes the degree of adaptation of deciduous fruit and nut species in Florida and identifies cultivars that are recommended for trial in various locations in Florida. Includes references. Originally published by the UF Department of Horticultural Sciences, November 2000. Revised February 2020.